TRIPS and the 1999 WTO Millennium Round : some reflections on future issues related to IPRs in the WTO and the way forward for developing countries - Watal, Jayashree (2000)
Discusses the issues likely to be raised in a future review of or in disputes on TRIPS and points out the important issues on IPRs for developing countries in the WTO.